Talent retention strategies and employees' behavioural outcomes: Empirical evidence from hospitality industry - Folakemi Ohunakin; Anthonia Adenike Adeniji; Gbenga Ogunlusi; Friday Igbadumhe; Adekunle Gabriel Sodeinde (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
To enhance the extant literature of talent retention and proffering solution to the negative employees' behavioural outcomes of high performers in hospitality industry, this study investigates the influence of talent retention strategies (training and development, and job security) on employees' behavioural outcomes (employee job performance and employee job commitment) in Nigeria's hospitality industry. Pen and paper questionnaire was used for gathering quantitative data among 312 frontline employees working in the selected 5-star hotels in Nigeria. Descriptive statistics, Confirmatory Factor Analysis (CFA), Structural Equation Modelling (SEM) and Path analysis were used to establish the mean, standard deviation, measuring instrument reliability, convergent, divergent and test of hypotheses respectively. The outcomes showed significant role of these retention strategies on employees' behavioural outcomes. This implies that, management should show consistent support for the career development and economic stability of their workforce, and most especially the professionals. This is highly important for gaining their full attention and positive workplace behaviour. This will create positive employer's branding, generate knowledge transfer, strengthen succession plan and retain top talents.
Keywords: M1; M5; M52; 650; training and development; job security; job commitment; job performance